PENGARUH METODE ACTIVE LEARNING TIPE QUIZ TEAM TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN FIQIH - Maghfirotul Itsna Khasanah; Ariga Bahrodin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Education is a crucial component in the process of molding the next generation of those who will govern the nation. With regard to the factors that contribute to the success of education, one of the most essential factors is the level of interest that students have in studying. Within the context of the MA Nurul Quran class X students, the objective of this study was to ascertain the impact that active learning strategies, which included quiz groups, have on the level of learning interest that they exhibit. In this study, a quantitative approach was used and an experimental design was used. The sample size consisted of thirty-five students. With a significance value of 0.000 which is smaller than the threshold of 0.05, the results of the study indicate that the implementation of this strategy has succeeded in increasing the level of students’ interest in learning. These findings indicate that the active learning approach of the quiz group type can be used to create an interesting and enjoyable atmosphere for learning, which in turn encourages students to be more involved and motivated in the fiqh learning process. Therefore, this strategy is believed to be more widely adopted in the field of education to improve the standard of education provided in madrasahs. The findings of this study also provide suggestions for teachers on how they can continue to develop new approaches in teaching to obtain the best results. In addition, it is hoped that the findings of this study will be a reference for potential future research in the field of education, especially those related to the implementation of active methods that have the potential to increase student involvement in the learning process.